Translating the architectural language of localities (Department of Architecture Faculty of Engineering Universitas Indonesia, 2025)
Architecture operates and conveys meaning through language, using such means to build spatial experience as well as invite new propositions and reconfiguration of spatialities. The collection of articles in this ARSNET issue explores the various contexts and applications of language in defining architectural localities. Exploring settings such as urban spaces and urban facilities, workplace environment, and even entirely new terrain, the architectural language of localities manifests through cultural and material practices, aesthetic embodiments, and speculative inquiries. Through this issue's investigation of language as creative methods of designing and experiencing space, the idea of localities becomes more dynamic, continuously speculated and reinterpreted across contexts and temporalities.